Front Cover: A Catalyst‐Free Cascade Reaction for the Selective Assembly of 3‐Hydroxyisoindolinones on Water (Asian J. Org. Chem. 11/2019). Issue 11 (29th October 2019) - Li, Pinyi; Jia, Xiuwen; Ma, Xiaoli; Ma, Wenbo; Sheng, Yilin; Zhao, Jingwei; Zhao, Fei
Abstract : The catalyst‐ and additive‐free cascade reactions between 2‐alkynylbenzoic acids and nitrogen‐containing nucleophiles on water form an efficient and selective method for the assembly of 3‐hydroxyisoindolinones. This protocol features readily available starting materials, an environmentally benign solvent, simple operation, extraordinarily broad substrate scope, good functional group tolerance, excellent selectivity, good to excellent yields, high atom‐ and step‐economy, and high bond‐forming efficiency, thus providing a convenient and highly efficient access to 3‐hydroxyisoindolinones. More information can be found in the Full Paper by Jingwei Zhao, Fei Zhao et al. on page 2073 in Issue 11, 2019 (DOI: 10.1002/ajoc.201900519 ).